The Impact of COVID-19 on the Returns of South African Exchange Traded Funds - Kunjal, Damien (Acta Universitatis Danubius. Œconomica, 2023)
The recent COVID-19 outbreak has created economic turmoil around the world. Given the soaring popularity of exchange traded funds in recent years, this study investigates the impact of COVID-19 on the returns of South African exchange traded funds. Using a sample period of March 5, 2020 to June 4, 2020, this study reports that, after controlling for alternative explanations of returns and conditional market volatility, the returns of exchange traded funds exhibit a significant, negative relationship with the growth in the total number of COVID-19 confirmed cases. On the contrary, the returns of exchange traded funds exhibit an insignificant, positive association with the growth in the total number of COVID-19 deaths.